Popular Hadiths of the Tablighi Jamaat Community (Reinterpretation Using a Historical-Contextual Approach) - Muhammad Irsad (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study discusses the traditions that are popular among the Tabligh Jamaah, focusing on three traditions; namely, the hadith about shaving the mustache and maintaining the beard, the hadith about wearing a white robe, and the hadith about using siwak. This research is a literature research, using a historical-contextual approach. The results of this study conclude that the traditions studied using the historical-contextual approach produce a new understanding that tends to be contradictory compared to the textual reading. The historical-contextual approach is able to present a more complex reading of the hadith, opening up the potential of Muslims to innovate with something more useful, as well as emphasizing the dividing line to distinguish between Islamic doctrine and the culture of Arab society which is the background of the decline and development of Islam.